Women’s Footwear Sole for the Elderly Produced with Sustainable Material: Friction Coefficient Analysis - dos Santos, Rosangela Monteiro; dos Santos, João Eduardo Guarnetti [UNESP]; Junior, Ademir Marques; Ventura, Flavio Cardoso; dos Santos, João Victor Gomes [UNESP]; Kovatch, Pedro Yuri; Paschoarelli, Luís Carlos [UNESP]; Medola, Fausto Orsi [UNESP] (Springer Nature, 2020)
One possibility to intervene in falls due to slipping is to use shoes with soles that can resist possible slips. The objective of this research is to evaluate the friction coefficient of the female footwear for the elderly produced with sustainable material (castor oil and bamboo composite). Slip tests on ceramic floors with a detergent solution and steel floors with glycerol solution (ABNT NBR ISO 20344: 2015, 5.11 and ISO 13287: 2012) were carried out at the Technological Research Institute of São Paulo (Brazil) - IPT. The results of the study showed that the sole developed with castor oil and bamboo is indicated for ceramic floors, but it is not advisable to use this kind of sole on steel floors with a glycerol solution.
Keywords: Biodegradable material; Elderly footwear; Friction coefficient; Slip; Sustainability